2017
DOI: 10.1515/jcim-2016-0066
|View full text |Cite
|
Sign up to set email alerts
|

Effects of luteolin and luteolin-morphine co-administration on acute and chronic pain and sciatic nerve ligated-induced neuropathy in mice

Abstract: Background Neuropathic pain (NP) is a common condition accompanied by nerve injury. To date, there is no definite treatment approved for this disorder. In addition, many drugs that are used for NP cause adverse reactions. Luteolin is a naturally occurring flavonoid with diverse pharmacological properties such as anti-inflammatory, antioxidant and anticancer. We sought to investigate luteolin effects on chronic, acute and neuropathic pain as well as its potential to increase morphine anti-nociceptive effects in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…In addition to diarrhoea, luteolin also reversed the mechanical hypersensitivity induced by irinotecan. Indeed, the anti‐nociceptive effects of luteolin have been described in several models of pain (Fan et al, ; Hashemzaei et al, ), highlighting the potential of the compound in pain management. Wardill et al () demonstrated that the hypersensitivity induced by irinotecan treatment is dependent on activation of TLR4.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to diarrhoea, luteolin also reversed the mechanical hypersensitivity induced by irinotecan. Indeed, the anti‐nociceptive effects of luteolin have been described in several models of pain (Fan et al, ; Hashemzaei et al, ), highlighting the potential of the compound in pain management. Wardill et al () demonstrated that the hypersensitivity induced by irinotecan treatment is dependent on activation of TLR4.…”
Section: Discussionmentioning
confidence: 99%
“…Natural products have attracted attention for their protective effects on the brain and heart caused via different mechanisms including antioxidant and antiinflammatory effects, and regulation of apoptosis and autophagy (Bastianetto et al , ; Hashemzaei et al , ; Hashemzaei et al , ; Sinha et al , ). Resveratrol (RES) (trans‐3, 4, 5‐trihydroxystilbene) is a natural polyphenolic phytoalexin that is found in black grape skin (Gu et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Natural products have attracted attention for their protective effects on the brain and heart caused via different mechanisms including antioxidant and antiinflammatory effects, and regulation of apoptosis and autophagy (Bastianetto et al, 2015;Hashemzaei et al, 2017a;Hashemzaei et al, 2017b;Sinha et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, this flavone can also be used in combination with these two classical treatment options to yield better results [ 124 ]. Beneficial effects induced by luteolin were also in a neuropathic pain model, where luteolin administration was found to reduce neuropathic pain, also potentiating the effects of morphine [ 125 ].…”
Section: Preclinical Pharmacological Activities Of Luteolin: In Vivo Evidencementioning
confidence: 99%